HIV Infection among Young People in Northwest Tanzania: The Role of Biological, Behavioural and Socio-Demographic Risk Factors. - Francesca Lemme; Aoife M Doyle; John Changalucha; Aura Andreasen; Kathy Baisley; Kaballa Maganja; Deborah Watson-Jones; Saidi Kapiga; Richard J Hayes; David A Ross (PLoS ONE)
Background Young people are at high risk of HIV and developing appropriate prevention programmes requires an understanding of the risk factors for HIV in this age group. We investigated factors associated with HIV among participants aged 15-30 years in a 2007-8 cross-sectional survey nested within a community-randomised trial of the MEMA kwa Vijana intervention in 20 rural communities in northwest Tanzania. Methods We analysed data for 7259(53%) males and 6476(47%) females. Using a proximate-determinant conceptual framework and conditional logistic regression, we obtained sex-specific Odds Ratios (ORs) for the association of HIV infection with socio-demographic, knowledge, behavioural and biological factors. Results HSV-2 infection was strongly associated with HIV infection (females: adjOR 4.4, 95%CI 3.2-6.1; males: adjOR 4.2, 95%CI 2.8-6.2). Several socio-demographic factors (such as age, marital status and mobility), behavioural factors (condom use, number and type of sexual partnerships) and biological factors (blood transfusion, lifetime pregnancies, genital ulcers, Neisseria gonorrhoeae) were also associated with HIV infection. Among females, lifetime sexual partners (linear trend, p<0.001), ≥2 partners in the past year (adjOR 2.0, 95%CI 1.4-2.8), ≥2 new partners in the past year (adjOR 1.9 95%CI 1.2, 3.3) and concurrent partners in the past year (adjOR 1.6 95%CI 1.1, 2.4) were all associated with HIV infection. Conclusions Efforts must be intensified to find effective interventions to reduce HSV-2. Effective behavioural interventions focusing on reducing the number of sexual partnerships and risk behaviour within partnerships are also needed. An increase in risky sexual behaviour may occur following marriage dissolution or when a young woman travels outside of her community and interventions addressing the needs of these subgroups of vulnerable women may be important. Trial registration ClinicalTrial.gov NCT00248469.